PERBAIKAN MUTU GENETIK UDANG GALAH (Macrobrachium rosenbergii) BERDASARKAN SELEKSI FAMILI [Genetic Improvement of Giant Freshwater Prawn (Macrobrachium rosenbergii) based on Family Selection] - Hadie, Lies Emmawati; Hadie, Wartono (BERITA BIOLOGI, 2012)
The base populations were composed to support selective breeding of giant freshwater prawn (Macrobrachium rosenbergii). Composite population were improved additive and dominance of genetic variance, especially for character of economic important. Economic character of giant freshwater prawn have a ratio of carapace length to standard length (ratio CL/SL).This research is aimed to improved the genetic of carapace and standard length ratio for giant freshwater prawn based on family selection. Selection methods were conducted on trait of carapace and standard length ratio as an edible portion. The base population prawn were used from three location i.e. Cimanuk (Cape of Air, West Java), Citanduy (Pamarican,West Java) and Musi River (Palembang, South Sumatra). Family selection was used selectedstructure. Parents were selected based on breeding value. Natural spawning was used product to first generation (F1) production of population. Larval rearing was used clear water system, fingerling production in the concrete tank, and juvenile rearing was conducted on earthen ponds. Respons selection was estimated to five months of freshwater prawn. Result of this experiment indicated that population of giant freshwater prawn can build by breeding program with heritability value of dressing out to 0.56+0.07; selection differential to 13.74 and selection intensity to 4.05. Prediction of genetic improvement from that genetic parameters is a value 7.69% to one generation. Implementation of population would be increased of genetic quality and there is decreased of gen degradation to prawn population.